The impacts of market reform on the market penetration of natural gas-fired electricity and renewable energy in China - Li-Jing Zhu (KeAi Communications Co., Ltd., 2017)
Abstract Natural gas-fired electricity (NGFE) is expected to play a more important role in the future due to its characteristics of low pollution, high efficiency and flexibility. However, its development in China is impeded by its high regulation price compared with coal power. Market reform is therefore of vital importance to promote the penetration of NGFE. The objective of this study is to analyze the impacts of market reform and the renewable electricity (RE) subsidy policy on the promotion of NGFE and RE. A dynamic game-theoretic model is developed to analyze the interaction among the NG supplier, the power sector and the power grid. Three scenarios are proposed with different policies, including a fixed regulation price of NG and electricity, real-time pricing (RTP) of NG and electricity, and subsidy targeted at RE. The results show that: (1) market reform can sharply decrease the NG price and consequently promote the development of NGFE and RE; (2) subsidy targeted at RE not only promotes the penetration of NGFE and RE, but also increases the utilization ratio of renewables significantly; (3) market reform and the subsidy also enhance consumers’ welfare by reducing their power consumption expenditure.